2015
DOI: 10.11646/phytotaxa.214.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A revision of Smallanthus (Asteraceae, Millerieae), the “yacón” genus

Abstract: Smallanthus (Asteraceae, Millerieae), the “yacón” genus, comprises 23 species ranging from southeastern United States to central Argentina, with the greatest diversity in Peru and Mexico. Species of Smallanthus are herbs, shrubs or small trees with tuberous roots, opposite, trinerved or triplinerved leaves, paleate receptacle, ray corollas externally hairy at the base, pappus lacking, and marginal cypselae partially embraced by the inner phyllaries of the involucre. As a result of this revision: Smallanthus ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
3
0
8
Order By: Relevance
“…Coll Aráoz et al, (2012); Vitali et al, (2015) Girasolcito, jaguarete, ka´a, yacón-gaúcho, yacón-nativo.…”
Section: S Connatusunclassified
See 3 more Smart Citations
“…Coll Aráoz et al, (2012); Vitali et al, (2015) Girasolcito, jaguarete, ka´a, yacón-gaúcho, yacón-nativo.…”
Section: S Connatusunclassified
“…Pecíolo: La morfología del pecíolo es muy variable entre las especies del género, hay pecíolos con alas grandes y anchas, con alas marcadamente atenuadas, y otras especies carecen de pecíolo (Vitali et al, 2015). Anatómicamente sin embargo, el pecíolo resultó ser homogéneo.…”
Section: S Uvedaliusunclassified
See 2 more Smart Citations
“…(Tribe Millerieae) consist of 23 species, distributed from the southeastern United States to east-central Argentina (Vitali & al., 2015). During taxonomic studies of the genus Smallanthus, it was found that the typification of Polymnia maculata Cav., the basionym of Smallanthus maculatus (Cav.)…”
Section: Introductionmentioning
confidence: 99%